2022
DOI: 10.1101/2022.11.09.515852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterozygous Inversion Breakpoints Suppress Meiotic Crossovers by Altering Recombination Repair Outcomes

Abstract: Heterozygous chromosome inversions suppress meiotic crossover (CO) formation within an inversion, potentially because they lead to gross chromosome rearrangements that produce inviable gametes. Interestingly, COs are also severely reduced in regions nearby but outside of inversion breakpoints even though COs in these regions do not result in rearrangements. Our mechanistic understanding of why COs are suppressed outside of inversion breakpoints is limited by a lack of data on the frequency of noncrossover gene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This raises the question of whether recombinational exchange in heterokaryotypes occurs at a sufficient rate that the condition T Sw = 1 is likely to hold. At least for simple inversions (with only a single pair of breakpoints) there is ample experimental evidence for recombination between In and St at sites within and adjacent to the inversion in species of Drosophila , much of which appears to be caused by gene conversion rather than double crossovers(Chovnick 1973; Korunes and Noor 2019; Li et al 2022; Koury 2023), with r = 10 -5 per basepair per generation being a commonly accepted typical rate (Chovnick 1973; Korunes and Noor 2019). Complex inversions, with three or more breakpoints, might be expected to have much lower rates of exchange than simple inversions, but heterozygotes for multiply inverted chromosomes in D. melanogaster have been found to experience non-crossover associated gene conversion events at rates that are even higher than in the absence of inversions (Crown et al 2018), so that this expectation may not be well founded.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This raises the question of whether recombinational exchange in heterokaryotypes occurs at a sufficient rate that the condition T Sw = 1 is likely to hold. At least for simple inversions (with only a single pair of breakpoints) there is ample experimental evidence for recombination between In and St at sites within and adjacent to the inversion in species of Drosophila , much of which appears to be caused by gene conversion rather than double crossovers(Chovnick 1973; Korunes and Noor 2019; Li et al 2022; Koury 2023), with r = 10 -5 per basepair per generation being a commonly accepted typical rate (Chovnick 1973; Korunes and Noor 2019). Complex inversions, with three or more breakpoints, might be expected to have much lower rates of exchange than simple inversions, but heterozygotes for multiply inverted chromosomes in D. melanogaster have been found to experience non-crossover associated gene conversion events at rates that are even higher than in the absence of inversions (Crown et al 2018), so that this expectation may not be well founded.…”
Section: Discussionmentioning
confidence: 99%
“…A major mechanism by which crossing over is suppressed or reduced in frequency during Drosophila female meiosis in heterozygotes for a paracentric inversion and the standard arrangement was elucidated by Sturtevant and Beadle (1936), whose genetic data suggested that single crossovers produce dicentric and acentric chromosomes that fail to be included in the egg nucleus. While several factors contribute to crossover suppression in inversion heterozygotes, with the conversion of double strand breaks into non-crossover associated gene conversion events playing an important role (Gong et al 2005; Crown et al 2018; Li et al 2022), there is no doubt that crossover suppression in inversion heterozygotes must cause different arrangements to become substantially genetically isolated from each other. Recent studies of heterozygous Drosophila inversions suggest a total suppression of crossing over within the regions covered by the inversion and for a substantial distance outside it (Li et al 2022; Koury 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations